2007
DOI: 10.1007/s10592-007-9413-0
|View full text |Cite
|
Sign up to set email alerts
|

Northwest passages: conservation genetics of Arctic Island wolves

Abstract: Wolves in the Canadian Arctic Archipelago face several challenges to persistence: a harsh habitat, an unstable prey base, and potentially significant anthropogenic influences. These external factors, if combined with genetic constraints common to island populations, could be particularly difficult to withstand. To determine the genetic status of Arctic Island wolves, we used 14 microsatellite loci to estimate population variation and the extent of interisland and island-mainland gene flow. All island populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
37
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 53 publications
(60 reference statements)
6
37
2
Order By: Relevance
“…Islands sampled for C. 1. arctos were grouped together in a neighbor-joining distance analysis based on autosomal microsatellite data (Carmichael et al 2008, figure 3B), but the authors observed that the island populations exhibited only one private allele, and that their unpublished mtDNA data did not identify any …”
Section: Canis Lupus Arctos (Arctic Wo#f) the Three High Arcticmentioning
confidence: 99%
“…Islands sampled for C. 1. arctos were grouped together in a neighbor-joining distance analysis based on autosomal microsatellite data (Carmichael et al 2008, figure 3B), but the authors observed that the island populations exhibited only one private allele, and that their unpublished mtDNA data did not identify any …”
Section: Canis Lupus Arctos (Arctic Wo#f) the Three High Arcticmentioning
confidence: 99%
“…Despite some taxonomic controversy regarding sub-species delineation, both cranial measures (Krizan 2005) and genetic data (Carmichael et al 2008) separate Arctic wolves from southern populations (Nowak 2003). While the grey wolf is one of the most wellstudied carnivores on Earth (Brooke et al 2014), ecological data on Arctic wolves are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, while some close relatives may be included in our study, we suggest the heterozygosity of TU9291 and SH9201's genotype makes identity through inbreeding unlikely. Furthermore, Carmichael et al (2007b) showed that inbreeding is rare or absent in this population.…”
mentioning
confidence: 81%
“…Bayesian estimation suggests a total, bi-directional migration rate of 1.76% between Banks Island and all northern mainland wolf populations (Western Woods; Forest; Western Barrens, including the Cape Bathurst region; Eastern Barrens; and Atlantic; Carmichael et al, 2007b), underscoring the unusual nature of this event.…”
mentioning
confidence: 94%
See 1 more Smart Citation